2003
DOI: 10.1136/gut.52.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Induction of experimental ulcerative colitis by Fusobacterium varium isolated from colonic mucosa of patients with ulcerative colitis

Abstract: Background: Bacteria are implicated in certain forms of model chronic colitis but the identity and role of bacteria in human ulcerative colitis (UC) are uncertain. Aims: To isolate pathogenic bacteria from inflamed mucosa of patients with UC, to examine whether the bacteria have a toxin to Vero cells, and to determine whether the toxin induces UC-like lesions in animals. Methods: Bacteria were isolated from UC patients and supernatants from cultures were filtered and tested for cytotoxicity to Vero cells. Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
200
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(206 citation statements)
references
References 33 publications
4
200
1
1
Order By: Relevance
“…We recently reported that culture supernatants from commensal bacteria (e.g., Fusobacterium varium) recovered from the inflamed mucosa of UC patients, induced UC-like lesions in mice (22,23). We have also observed that a combined antibiotic regimen directed against F. varium was effective in patients with active chronic UC (67).…”
Section: Resultsmentioning
confidence: 80%
“…We recently reported that culture supernatants from commensal bacteria (e.g., Fusobacterium varium) recovered from the inflamed mucosa of UC patients, induced UC-like lesions in mice (22,23). We have also observed that a combined antibiotic regimen directed against F. varium was effective in patients with active chronic UC (67).…”
Section: Resultsmentioning
confidence: 80%
“…To our knowledge, this is the first such report for a series of organic acids. Although we earlier reported that butyric acid at 32 mM was cytotoxic to Vero cells and induced apoptosis, 17 induction of p53 and downstream molecules regulating G1 checkpoint and activation of p53-dependent DNA repair were here demonstrated at a lower concentration in colorectal carcinomas and in UC-Ca-derived cell lines in vitro (Figs. 4a and 4b).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 These produce large amounts of organic acids, including short-chain fatty acids (SCFAs) and succinic acid. 18,19 SCFAs (such as butyrate, propionic acid and acetic acid) are important to maintain colonic functions, and butyrate, in particular, constitutes an energy supply for colonocytes and plays a central role in the homeostasis of the colonic mucosa.…”
mentioning
confidence: 99%
“…The normal gut microbiota carries out specific functions in host nutrient metabolism, xenobiotic and drug metabolism, structural integrity maintenance of the gut mucosal barrier, immunomodulation, and protection against pathogens 11, 12, 13, 14, 15. Recently, the gut microbiome has been shown to play a crucial role in health, as well as in diseases such as obesity,16 inflammatory bowel disease,17, 18 diabetes,19, 20 non‐alcoholic fatty liver disease,21, 22, 23 and several types of cancers 24, 25. Experimental evidence indicates that the human intestinal microbiome can influence tumor development and progression in the gastrointestinal tract by damaging DNA, activating oncogenic signaling pathways, producing tumor‐promoting metabolites, and suppressing the antitumor immune response 7, 25, 26, 27, 28, 29.…”
Section: Introductionmentioning
confidence: 99%